Indonesian Government's Budgeting Responses during the COVID-19 Pandemic: Multi-Level Governance and Actor-Network Theory Perspectives - Muliadi Muliadi; Aji Sofyan Effendi; Muhammad Ikbal (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2021)
Indonesia is one country affected by Covid-19. The Indonesian government has responded this outbreak by implementing an open policy, not a total lockdown as implemented in several countries in Asia and Europe. Our study aims at exploring the budget policy response to the crisis conditions caused by the Covid19. This study focuses on three main issues related to how the central government budget policy responds to the local government level, how the government policies provide a stimulus for the private sectors and MSMEs, and the concrete steps in handling the education aspect. A qualitative paradigm through a netnographic approach was used to analyze these three issues. The data were collected using both mass media content and document analysis within a period of 1 April -31 August 2020. The analysis instruments consisted of a multi-level governance and actor-network theory. the research findings show that technology as a non-human actor plays an important role in building humans in solving problems existing in the multi-level governance involving central government, local governments, MSMEs, and education sectors. This study may provide some contributions on how to deal with the state crises due to the pandemic and other consequences.